Gereja Hillsong Bali tahun 2017-2021 - A, Riswanti Febriani (Tantular, 2023)
Hillsong Church Bali is a Charismatic church which is one of the branches of Hillsong Church based in Sydney, Australia. Since its inception since 2017, Hillsong Bali Church is packaged differently from churches in general, starting from the way of worship that attracts a lot of attention of young people. This study aims to find out about the Bali Hillsong Church from 2017-2021 where this study uses the theory of sociology of religion and qualitative methods by using interviews to collect data from respondents who are members of the Bali Hillsong Church. The results showed that Bali was one of the missionary targets of Hillsong Church so that when Hillsong Bali Church was opened it did not take long to develop the church. Despite the Covid19 pandemic, which requires people to work from home, Hillsong Bali Church still reaches out to its congregations through social media such as YouTube worship broadcasts and also shares churchrelated information via Facebook and Instagram. The development of Hillsong Bali Church is increasing through the influence of social media which is actively used especially for tourists who are on vacation and looking for places of worship. The implications of the Hillsong Bali church for young people to worship consist of 3 main aspects where the Branding of the Hillsong Church which has many digital products, spiritual satisfaction in worshiping praise and worship and the Welcome Home and Come as You Are culture that is applied by church servants.